Soil Contamination in the Problem Areas of Agrarian Slovakia - Danica Fazekašová (MDPI AG, 2021)
Landfills, old and abandoned mines, industrial sites, heaps, sludge ponds and other sources of pollution represent environmental threats and are characterized as chemical time bombs. This work is focused on the evaluation of soil contamination by risk elements using various indices (geoaccumulation index—Igeo, enrichment factor—EF, contamination factor—Cif and degree of contamination—Cd). These selected agrarian problem areas are located in Slovakia, especially in the air pollution field of landfills consisting of power plant fly ash, tannery and footwear wastes, leachate (lúženec), iron ore slag, waste from metallurgy and sludge ponds in which coal sludge waste is deposited and waste from ore treatment. Nine research sites in the agrarian region of Slovak Republic were monitored. Ten risk elements (Fe, Mn, Zn, Cu, Co, Ni, Cr, Pb, Cd and Hg) and pH/H2O were included in this study and were determined in surface soils (of 0.05 m to 0.15 m) using atomic absorption spectrometry (AAS). Our study showed the highest exceedance of the limit values of risk elements in the order Ni (51.85 times) > Co (25.47 times) > Cd (13.70 times) > Cu (12.78 times) > Cr (8.37 times) > Fe (8.26 times) > Hg (7.94 times) > Zn (5.71 times) > Pb (4.63 times). The content of risk elements increased based on the average values of Igeo in the order of Cr < Hg < Zn < Pb < Ni < Cu < Cd. Igeo values for cadmium indicated mild-to-extreme contamination at all sites. We found the most significant enrichment in the order of Cd > Cu > Pb > Ni > Zn > Hg > Cr. EF values for cadmium indicated extremely high enrichment; the Cif and Cd values indicated a very high degree of soil contamination near the nickel smelter landfill, an industrial metallurgical plant and old but active mines. The studied areas pose a serious danger not only to the soil but also to groundwater and biota due to the prevailing low soil reaction, which increases the mobility of toxic elements. The study provides important results for the development of effective strategies for the control and remediation of endangered areas.